Formal verification of a CRT-RSA implementation against fault attacks - Christofi, Maria Dolores; Chetali, Boutheïna; Goubin, Louis; Vigilant, David (My University, 2013)
Cryptosystems are highly sensitive to physical attacks, which lead security developers to design more and more complex countermeasures. Nonetheless, no proof of flaw absence has been given for any implementation of these countermeasures. This paper aims to formally verify an implementation of one published countermeasure against fault injection attacks. More precisely, the formal verification concerns Vigilant's CRT-RSA countermeasure which is designed to sufficiently protect CRT-RSA implementations against fault attacks. The goal is to formally verify whether any possible fault injection threatening the pseudo-code is detected by the countermeasure according to a predefined attack model. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Countermeasures; Cryptographic implementation; Fault attacks; Formal verification; Frama-C; RSA-CRT